Chinese M&A in Germany - Liu, Yi-peng (Henry Stewart Talks, 2013)
Trends and development trajectory, Performance assessment of Chinese M&A in Germany, A process perspective: pre- and post-acquisition, Post-acquisition integration approaches, Recommendations for Chinese cross-border M&A, Prospects, challenges, and opportunities